Tumour Seeding After a Thoracic Biopsy for Renal Cell Carcinoma: A Case Report and a Review of the Literature. (June 2021) - Dionese, Michele; Basso, Umberto; Ramondo, Gaetano; Pierantoni, Francesco; Bimbatti, Davide; Caumo, Francesca; Zagonel, Vittorina; Maruzzo, Marco
The role of percutaneous tumour biopsies had gain importance in the management of renal cell carcinoma to provide diagnostic specimen for the patients with metastatic disease that could benefit a systemic treatment. Among the possible complications of this procedure, however, there is the risk of tumoral cells seeding along the biopsy's tract; this complication, albeit being reported as anecdotal, could have devastating effects. Here we report a case of a young male who developed subcutaneous chest metastasis of renal cell carcinoma after a biopsy of a lung nodule. We subsequently reviewed other cases reported in literature